Character Education for Adults: A Visionary Look at Future Education Concepts - Lutfi, Saiful; Pelu, Ibnu Elmi A. S. (International Journal of Education, Culture, and Society, 2025)
Character education is often associated with children and young people, but adults need it too. In modern challenging life, adults face various problems, such as social pressure, family responsibilities, and the demands of the workforce. If not equipped with good character education, they can experience a moral crisis, lose their identity, and have difficulty making wise decisions. This research uses the qualitative descriptive method to explore the importance of character education for adults and the right approach to its implementation. The results show that character education can help individuals become more responsible, have integrity, and be able to face the changing times with a wise attitude. In addition, character education also plays an important role in guiding adults to make positive use of technology and not get caught up in the negative impacts of digitalization. With the right approach, character education can be a solution in creating stronger, more independent individuals who are able to set an example for the next generation.